2018
DOI: 10.1096/fj.201800458
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor I blockade prevents stenosis of tissue engineered vascular grafts

Abstract: We previously developed a tissue-engineered vascular graft (TEVG) made by seeding autologous cells onto a biodegradable tubular scaffold, in an attempt to create a living vascular graft with growth potential for use in children undergoing congenital heart surgery. Results of our clinical trial showed that the TEVG possesses growth capacity but that its widespread clinical use is not yet advisable due to the high incidence of TEVG stenosis. In animal models, TEVG stenosis is caused by increased monocytic cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Experimental work suggested that higher seeding densities may mitigate graft stenosis ( 160 , 161 ). Alternatively, pharmacological interventions were tested emulating the previously tried ACE inhibitor therapy ( 165 ) with modern angiotensin II receptor blockade ( 166 ). Eventually, single stage seeding of degradable scaffolds was carried over to heart valves and tested in acute ( 167 ) and semi-acute ( 168 ) sheep implants.…”
Section: A Protracted Evolutionmentioning
confidence: 99%
“…Experimental work suggested that higher seeding densities may mitigate graft stenosis ( 160 , 161 ). Alternatively, pharmacological interventions were tested emulating the previously tried ACE inhibitor therapy ( 165 ) with modern angiotensin II receptor blockade ( 166 ). Eventually, single stage seeding of degradable scaffolds was carried over to heart valves and tested in acute ( 167 ) and semi-acute ( 168 ) sheep implants.…”
Section: A Protracted Evolutionmentioning
confidence: 99%
“…Compared to the unseeded control, the BM‐MNC seeded grafts showed elevated patency rates, concentric layers of aligned SMCs, a confluent EC monolayer, and collagen‐rich ECM. [ 68,69 ] These observations correlate with less platelet adhesion, [ 101 ] less platelet activation (as measured in terms of platelet‐derived ATP), less macrophage infiltration, and a higher ratio of M2 macrophages in the seeded graft. [ 102 ] The BM‐MNCs were found to secrete MCP‐1, which enhanced monocyte recruitment during the first week after implantation.…”
Section: Immunomodulation In Building Tissue Engineered Vascular Graftsmentioning
confidence: 99%
“…(C) an incomplete endothelium and a mismatch in the mechanical properties with a flow disturbance will induce the activation of a synthetic phenotype in SMCs, that will overproliferate and decrease the vessel lumen [17]. (D) The lack in the mechanical properties of the TEVG required for specific hemodynamic conditions or a faster biodegradability rate than the vascular wall regeneration is expected to cause aneurysms [18,19]. (E) A slower biodegradability rate than the vascular wall regeneration is likely to cause a higher influx of pro-inflammatory cells, that might lead to a dysregulated balance between the synthesis and the degradation of the novo extracellular matrix, and if there is a chronic inflammatory stimulus, atherogenesis can occur with calcium and phosphate deposition in the disorganized tissue [20].…”
Section: Phases Of the Vascular Graft Responsementioning
confidence: 99%